Assessing parents' receptiveness to a vegetable-focussed in-school nutrition intervention. (1st October 2017) - Jongenelis, Michelle I.; Pettigrew, Simone; Pratt, Iain S.; Wright, Shannon; Myers, Gael
Abstract: Objective: Crunch&Sip is an Australian school-based initiative designed to increase the consumption of fruit, vegetables, and water among primary school children. To address the significant deficiencies in children's vegetable intake, the present study aimed to examine the responsiveness of parents (the main providers of food for Crunch&Sip) to a modified version of the program that focuses primarily on vegetable consumption. Participants: A total of 329 Western Australian parents completed an online questionnaire examining their support for a vegetable focus for Crunch&Sip and any perceived barriers, motivators, and facilitators. Results: Most (80%) parents were supportive of a shift to a vegetable focus for Crunch&Sip. Belief in the effectiveness of Crunch&Sip at improving children's attitudes towards vegetables and increasing children's vegetable consumption was found to be significantly associated with levels of support. The most commonly nominated motivator was to improve their children's eating habits and the main facilitator was the perceived ability of teachers and peers to influence children's food consumption behaviours. Identified potential barriers included the difficulties associated with providing a variety of vegetables, maintaining freshness, and the preparation time required. The primary suggested strategy to overcome these barriers was for schools to conduct education sessions to provide information about vegetable provision options. Conclusions and implications: The results suggest that parents can be supportive of school-based nutrition programs that specifically encourage the consumption of vegetables but they may require guidance to reduce the identified barriers related to vegetable provision.